Low-temperature synthesis method of nano fluorescent powder based on BaO-SiO2 system
By synthesizing the nano-crystal of BAH2SIO4 in the alcohol water solution, and burning with hydroxide at low temperature, it solves the problem of difficulty in synthesizing without miscellaneous nano-SIO2 fluorescent powder in existing technologies, realizing low temperature synthetic nanofluorescence powder. Methods to improve craftsmanship and performance.
Patent Information
- Application Number
- CN202411458069.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-21
AI Technical Summary
现有技术难以在低温条件下合成无杂相、纳米级的BaO-SiO2体系荧光粉,且高温煅烧导致粉体颗粒大、不均匀,容易产生色斑。
In the alcohol water solution, the nanocrystal of BAH2SIO4 is directly synthesized, and the nano-fluorescent powder of the BAO-SIO2 system is synthesized at low temperature with the residual hydroxide.
Achieve silicate fluorescent powder with excellent nano -level performance under low temperature conditions. It has simple craftsmanship, low equipment requirements, saving energy consumption, and good product.
Smart Images

Figure CN119331603A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nano oxide preparation, and specifically relates to a nano oxide preparation method based on BaO-SiO 2 A low-temperature synthesis method for nano-phosphors based on a system. Background Art
[0002] As the phosphor matrix material, the silicate system is easy to adjust the composition and has excellent water resistance, thermal stability and chemical stability. From the early days of phosphor development to the present, the research has been hot. As the phosphor matrix, its advantages are self-evident. Among the silicate phosphor matrices, alkaline earth metal silicates are the most common. Among them, BaO-SiO 2 The matrix luminescence performance of the system is the most outstanding. They are the most widely used silicate and phosphors, and have a research history of more than 40 years.
[0003] Usually rare earth doped BaO-SiO 2 The preparation method of the luminescent powder of the system is to use a high temperature solid phase method. Generally, BaCO 3 、SiO 2 、Eu 2 O 3 etc. as raw materials, after grinding and mixing, calcined at ~1100℃, and finally calcined at ~1400℃ with hydrogen. The high temperature solid phase method has significant advantages such as simple preparation method, low cost, and large-scale synthesis. However, the synthesis process requires high temperature conditions, high energy consumption, and large phosphor particles, which reduces the processability of the powder and is even prone to color spots in specific applications, limiting its use in some applications with high particle size requirements.
[0004] Another common method is the sol-gel method, which usually uses soluble inorganic salts or organic alcohol salts as raw materials, forms a sol in the solution, forms a dry gel after drying, and then calcined at high temperature to obtain the desired product. Compared with the high-temperature solid phase method, the material particles are uniform and fine, and the synthesis temperature is lower, but the luminous efficiency of the product will become lower and the preparation process is complicated. There are also some other methods such as hydrothermal method and coprecipitation method, which still have difficulties to overcome in the preparation of silicates and have not become mainstream.
[0005] Because the silicon-oxygen bond in silicates is a covalent bond, unlike most other oxides, the migration of lattice cations is difficult. For rare earth ion doping, using conventional processes, it will be difficult for impurity ions to enter the lattice and be evenly distributed in the lattice. For this reason, phosphors have to use higher calcination temperatures or use low melting point fluxes such as B 2 O 3. These measures will make the powder grains coarse and uneven in size, which will easily cause color spots and deteriorate the processability of the phosphor. Due to the complexity of the silicate system, whether it is a high-temperature solid-phase method or a sol-gel condensation method, impurities are very likely to appear during the calcination process. So far, it is still a major challenge for silicate phosphors to be free of impurities, have uniform and fine powders, especially at the nanoscale, and have fluorescent activators such as rare earth ions evenly distributed on the lattice.
[0006] Therefore, in order to solve the above difficulties, a simple and effective method is needed to synthesize BaO-SiO 2 This method directly synthesizes BaH in alcohol-water solution. 2 SiO 4 This step is crucial for the subsequent process. Tetraethyl orthosilicate is easy to form water glass colloid. Once this happens, the powder will become hard particles and all aspects of performance will be seriously reduced. 2 SiO 4 The nanocrystals are then calcined with the residual barium hydroxide at low temperature to synthesize BaO-SiO 2 A new synthesis method for nano phosphors of the system can obtain nano-scale silicate phosphors with excellent performance without high-temperature calcination. The process is simple, the equipment requirements are low, the synthesis efficiency is high, and the product has good processability. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention aims to provide a method for preparing nano-scale silicate phosphors with simple process, low cost and good performance, and in particular to a method for directly synthesizing BaH 2 SiO 4 The nanocrystals are then calcined with the residual barium hydroxide at low temperature to synthesize BaO-SiO 2 The method for synthesizing nano-phosphors of the system comprises adding rare earth nitrate and tetraethyl orthosilicate to a suitable alcohol in a certain proportion, and then adding the mixture to a water-alcohol mixed solution containing barium hydroxide and having a suitable proportion, stirring and hydrolyzing at a certain temperature, and continuing the reaction for a certain time to directly synthesize BaH in the solution. 2 SiO 4 The nanocrystals are then calcined with the residual barium hydroxide at low temperature to synthesize BaO-SiO 2 Nano phosphors of the system.
[0008] A BaO-SiO-based 2 The low-temperature synthesis method of nano-phosphor powder of the system specifically comprises the following steps:
[0009] (1) dissolving tetraethyl orthosilicate and a salt of an activator element in alcohol to prepare liquid A;
[0010] (2) grinding barium hydroxide, adding it to alcohol or a mixed solvent of alcohol and water to prepare liquid B, and heating it;
[0011] (3) Liquid A is added dropwise to the above-mentioned liquid B for reaction. During the dropwise addition process, the system temperature is maintained and stirring is continued. After the titration of liquid A is completed, the reaction is continued for a period of time, and the system is allowed to stand. Then, the solvent is removed from the system to obtain a solid phase, the composition of which is BaH 2 SiO 4 nanocrystals and residual barium hydroxide;
[0012] (4) The obtained solid phase is calcined and then kept warm to obtain nano phosphor powder.
[0013] in:
[0014] In the step (1), the activator elements are rare earth elements such as Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, and Yb, and transition elements such as V, Cr, and Mn.
[0015] In the step (1), the salt of the activator element refers to an organic acid salt or an inorganic acid salt of the activator element, the organic acid is formic acid or acetic acid, and the inorganic acid is sulfuric acid, hydrochloric acid or nitric acid.
[0016] In the steps (1) and (2), the alcohol is a pure solution selected from one or more of ethanol, ethylene glycol, propanol, glycerol, and butanol. When multiple alcohols are selected, the multiple alcohols can be in any proportion.
[0017] In the step (1), the mass ratio between tetraethyl orthosilicate and alcohol is (0.01-50):1.
[0018] In the step (2), the ratio of the molar number of the added barium hydroxide to the molar number of the ethyl orthosilicate in the step (1) is set according to the Ba:Si ratio in the target silicate.
[0019] In the step (2), the mass ratio of barium hydroxide to alcohol or alcohol-water mixed solvent is (0.01-10):1; in the alcohol or alcohol-water mixed solvent, the mass of water is 0-35% of the mass fraction of the alcohol.
[0020] In the step (2), the heating temperature is 40 to 90° C. and the heating time is 20 to 600 min.
[0021] In the step (3), the ratio of the salt of the activator element in the A solution to the barium hydroxide in the B solution is: the percentage of the molar number of metal ions in the salt of the activator element to the molar number of barium hydroxide is 0.05-10%.
[0022] In the step (3), the reaction time is 20 to 600 minutes, and the standing time is 1 to 48 hours.
[0023] In the step (3), the solvent is removed by evaporation, vacuum drying, centrifugal separation or filter press.
[0024] In the step (4), the calcination temperature is 500 to 1200° C., and the insulation time is 60 to 600 minutes.
[0025] In the step (4), when the activator cations in the solid phase need to be reduced, the calcination is carried out under a protective atmosphere, or a reducing agent is mixed into or placed beside the solid phase;
[0026] The protective atmosphere is nitrogen, hydrogen or argon;
[0027] The reducing agent is aluminum powder, iron powder or carbon powder. When carbon powder is used as the reducing agent, the carbon powder is mixed with the solid phase or used aside. When other reducing agents are used, they must be used aside. Calculated by mass fraction, the amount of reducing agent added shall not exceed 20% of the solid phase.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The present invention directly synthesizes BaH in alcohol-water solution 2 SiO 4 Nanocrystals are then calcined with residual barium hydroxide to synthesize BaO-SiO 2 The nano-phosphors of the system can be synthesized by low-temperature calcination to obtain the required pure-phase silicate nano-phosphors, while the usual methods require high-temperature treatment of about 1400°C.
[0030] 2. The low-temperature calcination synthesis adopted in this method not only greatly improves the performance and saves energy consumption, but also avoids the grain growth of the powder caused by high temperature, laying a good foundation for the subsequent application of the powder.
[0031] 3. The present invention is easy to operate and is easy to synthesize pure phase and large-scale nano fluorescent powder; the synthesized nano powder has uniform particle size and the processability of the powder is greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 XRD patterns of samples synthesized in solutions of Examples 1-5 of the present invention;
[0033] Figure 2 SEM images of samples synthesized in solutions of Examples 1-5 of the present invention;
[0034] Figure 3 XRD patterns of the nano-phosphors prepared in Examples 1 and 3 of the present invention;
[0035] Figure 4 SEM image of the nano phosphor prepared in Example 1 of the present invention;
[0036] Figure 5 PL spectra of the nano-phosphors prepared in Examples 1-5 of the present invention;
[0037] Figure 6 XRD patterns of the nano-phosphors prepared in Examples 6, 7, 10, 11 and 16 of the present invention;
[0038] Figure 7 SEM image of the nano phosphor prepared in Example 6 of the present invention;
[0039] Figure 8 PL spectra of the nano-phosphors prepared in Examples 8-12 of the present invention;
[0040] Fig. 9 SEM image of the nano phosphor prepared in Example 13 of the present invention;
[0041] Fig.10 PL spectra of the nano-phosphors prepared in Examples 13-16 of the present invention. DETAILED DESCRIPTION
[0042] The invention will be further described below in conjunction with embodiments:
[0043] Example 1
[0044] A BaO-SiO-based 2 The low-temperature synthesis method of nano-phosphor powder of the system specifically comprises the following steps:
[0045] (1) Weigh EuCl 3 6H 2 O 0.036g, measure 2.24mL of tetraethyl orthosilicate, add 30mL of anhydrous ethanol, dissolve and prepare liquid A, wherein the mass ratio of tetraethyl orthosilicate to alcohol is 0.04:1;
[0046] (2) Weigh 3.15 g Ba(OH) in a beaker 2 8H 2 O, added to a mixed solution of 15 mL of water and 30 mL of anhydrous ethanol, heated in a water bath at 80 °C and stirred for 30 min to obtain solution B; wherein Ba(OH) 2 8H 2 The mass ratio of O to alcohol-water solvent is 0.05:1. In terms of mass fraction, the mass of water is 32% of that of alcohol;
[0047] (3) Add liquid A dropwise into the above liquid B, stir rapidly, and maintain the system temperature during the addition process. 3+The percentage of the molar number of barium hydroxide in liquid B is 1%. After the titration of liquid A is completed, the reaction is carried out for 2 hours, and then it is allowed to stand for 24 hours. After centrifugation for 20 minutes and solid-liquid separation, a solid phase is obtained, which is placed in a drying oven for drying. After complete drying, it is ground with a mortar to obtain a powder. The XRD of the obtained powder is as follows Figure 1 As shown in the figure, it can be seen that the main peak of the sample is consistent with BaH 2 SiO 4 The peaks are basically consistent, and the SEM of the obtained powder is as follows Figure 2 As shown in the figure, it can be seen that there are many fine particles with a grain size of nanometers;
[0048] (4) The obtained powder was sintered in a muffle furnace at 500°C and kept at this temperature for 2 h, and then cooled to room temperature to obtain a nano-phosphor powder. The XRD, SEM, and PL spectra thereof were measured, as shown in FIG. Figure 3 , 4 , 5. From Figure 3 It can be seen that the peak of the sintered sample is similar to that of BaSiO 3 The correspondence is very good, indicating that pure BaSiO 3 .from Figure 4 It can be seen that the powder particles are very small and evenly distributed, and the agglomeration phenomenon is not obvious. Figure 5 As shown, the characteristic red color of trivalent europium ions is displayed.
[0049] Example 2
[0050] A BaO-SiO-based 2 The low-temperature synthesis method of nano-phosphor powder of the system specifically comprises the following steps:
[0051] (1) Weigh EuCl 3 6H 2 O 0.036g, measure 2.24mL of tetraethyl orthosilicate, add 30mL of anhydrous ethanol, dissolve and prepare liquid A, wherein the mass ratio of tetraethyl orthosilicate to alcohol is 0.04:1;
[0052] (2) Weigh 3.15 g Ba(OH) in a beaker 2 8H 2 O, added to a mixed solution of 15 mL of water and 30 mL of anhydrous ethanol, heated in a water bath at 80 °C and stirred for 30 min to obtain solution B; wherein Ba(OH) 2 8H 2 The mass ratio of O to alcohol-water solvent is 0.05:1. In terms of mass fraction, the mass of water is 32% of that of alcohol;
[0053] (3) Add liquid A dropwise into the above liquid B, stir rapidly, and maintain the system temperature during the addition process. 3+The percentage of the molar number of barium hydroxide in liquid B is 1%. After the titration of liquid A is completed, the reaction is carried out for 2 hours, and then it is allowed to stand for 24 hours. After centrifugation for 20 minutes and solid-liquid separation, a solid phase is obtained, which is placed in a drying oven for drying. After complete drying, it is ground with a mortar to obtain a powder. The XRD of the obtained powder is as follows Figure 1 As shown in the figure, it can be seen that the main peak of the sample is consistent with BaH 2 SiO 4 The peaks are basically consistent, and the SEM of the obtained powder is as follows Figure 2 As shown in the figure, it can be seen that there are many fine particles with a grain size of nanometers;
[0054] (4) The obtained powder was sintered in a muffle furnace at 600°C and kept at this temperature for 2 h, and then cooled to room temperature to obtain a nano-phosphor powder. The XRD, SEM, and PL spectra of the nano-phosphor powder were measured. Figure 3 The XRD patterns of the samples sintered at 500℃ are similar to those of BaSiO 3 The correspondence is very good, indicating that pure BaSiO 3 . SEM images and Figure 4 The powder particles are very small and evenly distributed, and the agglomeration phenomenon is not obvious. Figure 5 As shown, the characteristic red color of trivalent europium ions is displayed.
[0055] Example 3
[0056] A BaO-SiO-based 2 The low-temperature synthesis method of nano-phosphor powder of the system specifically comprises the following steps:
[0057] (1) Weigh EuCl 3 6H 2 O 0.036g, measure 2.24mL of tetraethyl orthosilicate, add 30mL of anhydrous ethanol, dissolve and prepare liquid A, in which the mass ratio of tetraethyl orthosilicate to alcohol is 0.04:1;
[0058] (2) Weigh 3.15 g Ba(OH) in a beaker 2 8H 2 O, added to a mixed solution of 15 mL of water and 30 mL of anhydrous ethanol, heated in a water bath at 80 °C and stirred for 30 min to obtain solution B; wherein Ba(OH) 2 8H 2 The mass ratio of O to alcohol-water solvent is 0.05:1. In terms of mass fraction, the mass of water is 32% of that of alcohol;
[0059] (3) Add liquid A dropwise into the above liquid B, stir rapidly, and maintain the system temperature during the addition process. 3+The percentage of the molar number of barium hydroxide in liquid B is 1%. After the titration of liquid A is completed, the reaction is carried out for 2 hours, and then it is allowed to stand for 24 hours. After centrifugation for 20 minutes and solid-liquid separation, a solid phase is obtained, which is placed in a drying oven for drying. After complete drying, it is ground with a mortar to obtain a powder. The XRD of the obtained powder is as follows Figure 1 As shown in the figure, it can be seen that the main peak of the sample is consistent with BaH 2 SiO 4 The peaks are basically consistent, and the SEM of the obtained powder is as follows Figure 2 As shown in the figure, it can be seen that there are many fine particles with a grain size of nanometers;
[0060] (4) The obtained powder was sintered in a muffle furnace at 700°C and kept at this temperature for 2 h, and then cooled to room temperature to obtain a nano-phosphor powder. The XRD, SEM, and PL spectra thereof were measured. The XRD spectrum was as follows: Figure 3 As shown, the peak of the sintered sample is similar to that of BaSiO 3 The correspondence is very good, indicating that pure BaSiO 3 , SEM images and Figure 4 The powder particles are very small and evenly distributed, and the agglomeration phenomenon is not obvious. Figure 5 As shown, the characteristic red color of trivalent europium ions is displayed.
[0061] Example 4
[0062] A BaO-SiO-based 2 The low-temperature synthesis method of nano-phosphor powder of the system specifically comprises the following steps:
[0063] (1) Weigh EuCl 3 6H 2 O 0.036g, measure 2.24mL of tetraethyl orthosilicate, add 30mL of anhydrous ethanol, dissolve and prepare liquid A, wherein the mass ratio of tetraethyl orthosilicate to alcohol is 0.04:1;
[0064] (2) Weigh 3.15 g Ba(OH) in a beaker 2 8H 2 O, added to a mixed solution of 15 mL of water and 30 mL of anhydrous ethanol, heated in a water bath at 80 °C and stirred for 30 min to obtain solution B; wherein Ba(OH) 2 8H 2 The mass ratio of O to alcohol-water solvent is 0.05:1. In terms of mass fraction, the mass of water is 32% of that of alcohol;
[0065] (3) Add liquid A dropwise into the above liquid B, stir rapidly, and maintain the system temperature during the addition process. 3+The percentage of the molar number of barium hydroxide in liquid B is 1%. After the titration of liquid A is completed, the reaction is carried out for 2 hours, and then it is allowed to stand for 24 hours. After centrifugation for 20 minutes and solid-liquid separation, a solid phase is obtained, which is placed in a drying oven for drying. After complete drying, it is ground with a mortar to obtain a powder. The XRD of the obtained powder is as follows Figure 1 As shown in the figure, it can be seen that the main peak of the sample is consistent with BaH 2 SiO 4 The peaks are basically consistent, and the SEM of the obtained powder is as follows Figure 2 As shown in the figure, it can be seen that there are many fine particles with a grain size of nanometers;
[0066] (4) The obtained powder was sintered in a muffle furnace at 800°C and kept at this temperature for 2 h, and then cooled to room temperature to obtain a nano-phosphor powder. The XRD, SEM, and PL spectra of the nano-phosphor powder were measured. Figure 3 The XRD results of the samples sintered at 700℃ are similar to those of BaSiO 3 The correspondence is very good, indicating that pure BaSiO 3 . SEM images and Figure 4 The powder particles are very small and evenly distributed, and the agglomeration phenomenon is not obvious. Figure 5 As shown, the characteristic red color of trivalent europium ions is displayed.
[0067] Example 5
[0068] A BaO-SiO-based 2 The low-temperature synthesis method of nano-phosphor powder of the system specifically comprises the following steps:
[0069] (1) Weigh EuCl 3 6H 2 O 0.036g, measure 2.24mL of tetraethyl orthosilicate, add 30mL of anhydrous ethanol, dissolve and prepare liquid A, wherein the mass ratio of tetraethyl orthosilicate to alcohol is 0.04:1;
[0070] (2) Weigh 3.15 g Ba(OH) in a beaker 2 8H 2 O, added to a mixed solution of 15 mL of water and 30 mL of anhydrous ethanol, heated in a water bath at 80 °C and stirred for 30 min to obtain solution B; wherein Ba(OH) 2 8H 2 The mass ratio of O to alcohol-water solvent is 0.05:1. In terms of mass fraction, the mass of water is 32% of that of alcohol;
[0071] (3) Add liquid A dropwise into the above liquid B, stir rapidly, and maintain the system temperature during the addition process. 3+The percentage of the molar number of barium hydroxide in liquid B is 1%. After the titration of liquid A is completed, the reaction is carried out for 2 hours, and then it is allowed to stand for 24 hours. After centrifugation for 20 minutes and solid-liquid separation, a solid phase is obtained, which is placed in a drying oven for drying. After complete drying, it is ground with a mortar to obtain a powder. The XRD of the obtained powder is as follows Figure 1 As shown in the figure, it can be seen that the main peak of the sample is consistent with BaH 2 SiO 4 The peaks are basically consistent, and the SEM of the obtained powder is as follows Figure 2 As shown in the figure, it can be seen that there are many fine particles with a grain size of nanometers;
[0072] (4) The obtained powder was sintered in a muffle furnace at 900°C and kept at this temperature for 2 h, and then cooled to room temperature to obtain a nano-phosphor powder. The XRD, SEM, and PL spectra of the nano-phosphor powder were measured. Figure 3 The XRD results of the samples sintered at 700℃ are similar to those of BaSiO 3 The correspondence is very good, indicating that pure BaSiO 3 . SEM images and Figure 4 The powder particles are very small and evenly distributed, and the agglomeration phenomenon is not obvious. Its PL spectrum is as follows Figure 5 As shown, the characteristic red color of trivalent europium ions is displayed.
[0073] Example 6
[0074] A BaO-SiO-based 2 The low-temperature synthesis method of nano-phosphor powder of the system specifically comprises the following steps:
[0075] (1) Weigh EuCl 3 6H 2 O 0.072g, measure 1.12mL of tetraethyl orthosilicate, add 30mL of anhydrous ethanol, dissolve and prepare liquid A, in which the mass ratio of tetraethyl orthosilicate to alcohol is 0.02:1;
[0076] (2) Weigh 3.15 g Ba(OH) in a beaker 2 8H 2 O, added to a mixed solution of 15 mL of water and 30 mL of anhydrous ethanol, heated in a water bath at 80 °C and stirred for 30 min to obtain solution B; wherein Ba(OH) 2 8H 2 The mass ratio of O to alcohol-water solvent is 0.05:1. In terms of mass fraction, the mass of water is 32% of that of alcohol;
[0077] (3) Add liquid A dropwise into the above liquid B, stir rapidly, and maintain the system temperature during the addition process. 3+The percentage of the molar number of barium hydroxide in liquid B is 2%. After the titration of liquid A is completed, react for 2 hours, let it stand for 24 hours, centrifuge for 20 minutes and separate the solid and liquid to obtain a solid phase, put it in a drying oven for drying, and grind it in a mortar to obtain a powder after it is completely dried.
[0078] (4) The obtained powder was sintered in a muffle furnace at 700°C and kept at this temperature for 2 h, and then cooled to room temperature to obtain a nano-phosphor powder. The XRD, SEM, and PL spectra thereof were measured. The XRD spectrum was as follows: Figure 6 As shown, the diffraction peaks all correspond well to the standard card, indicating that after sintering, the sample is transformed into a pure phase Ba 2 SiO 4 The SEM image is as follows: Figure 7 As shown in the figure, it can be seen that after sintering at 700℃, the powder is very fine and the grain size is very small, only a dozen nanometers. Figure 8 Similarly, the characteristic red color of trivalent europium ions is displayed.
[0079] Example 7
[0080] A BaO-SiO-based 2 The low-temperature synthesis method of nano-phosphor powder of the system specifically comprises the following steps:
[0081] (1) Weigh EuCl 3 6H 2 O 0.072g, measure 1.12mL of tetraethyl orthosilicate, add 30mL of anhydrous ethanol, dissolve and prepare liquid A, wherein the mass ratio of tetraethyl orthosilicate to alcohol is 0.02:1;
[0082] (2) Weigh 3.15 g Ba(OH) in a beaker 2 8H 2 O, added to a mixed solution of 15 mL of water and 30 mL of anhydrous ethanol, heated in a water bath at 80 °C and stirred for 30 min to obtain solution B; wherein Ba(OH) 2 8H 2 The mass ratio of O to alcohol-water solvent is 0.05:1. In terms of mass fraction, the mass of water is 32% of that of alcohol;
[0083] (3) Add liquid A dropwise into the above liquid B, stir rapidly, and maintain the system temperature during the addition process. 3+ The percentage of the molar number of barium hydroxide in liquid B is 2%. After the titration of liquid A is completed, react for 2 hours, let it stand for 24 hours, centrifuge for 20 minutes and separate the solid and liquid to obtain a solid phase, put it in a drying oven for drying, and grind it in a mortar to obtain a powder after it is completely dried.
[0084] (4) The obtained powder was sintered in a muffle furnace at 800°C and kept at this temperature for 2 h, and then cooled to room temperature to obtain a nano-phosphor powder. The XRD, SEM, and PL spectra thereof were measured. The XRD spectrum was as follows: Figure 6 As shown, the diffraction peaks all correspond well to the standard card, indicating that after sintering, the sample is transformed into a pure phase Ba 2 SiO 4 The higher the sintering temperature, the better the sample peak correspondence and the more main peak phases. Figure 7 It can be seen that after sintering at 800℃, the powder is very fine and the grain size is very small, only a dozen nanometers. Figure 8 Similarly, the characteristic red color of trivalent europium ions is displayed.
[0085] Example 8
[0086] A BaO-SiO-based 2 The low-temperature synthesis method of nano-phosphor powder of the system specifically comprises the following steps:
[0087] (1) Weigh EuCl 3 6H 2 O 0.036g, measure 1.12mL of tetraethyl orthosilicate, add 30mL of anhydrous ethanol, and dissolve to obtain liquid A, wherein the mass ratio of tetraethyl orthosilicate to alcohol is 0.02:1;
[0088] (2) Weigh 3.15 g Ba(OH) in a beaker 2 8H 2 O, added to a mixed solution of 15 mL of water and 30 mL of anhydrous ethanol, heated in a water bath at 80 °C and stirred for 30 min to obtain solution B; wherein Ba(OH) 2 8H 2 The mass ratio of O to alcohol-water solvent is 0.05:1. In terms of mass fraction, the mass of water is 32% of that of alcohol;
[0089] (3) Add liquid A dropwise into the above liquid B, stir rapidly, and maintain the system temperature during the addition process. 3+ The percentage of the molar number of barium hydroxide in liquid B is 1%. After the titration of liquid A is completed, react for 2 hours, let it stand for 24 hours, centrifuge for 20 minutes and separate the solid and liquid to obtain a solid phase, put it in a drying oven for drying, and grind it in a mortar to obtain a powder after it is completely dried.
[0090] (4) The obtained powder was sintered in a muffle furnace at 500°C and kept at this temperature for 2 h, and then cooled to room temperature to obtain a nano-phosphor powder. The PL spectrum thereof was measured. Figure 8 As shown, the characteristic red color of trivalent europium ions is displayed.
[0091] Example 9
[0092] A BaO-SiO-based 2 The low-temperature synthesis method of nano-phosphor powder of the system specifically comprises the following steps:
[0093] (1) Weigh EuCl 3 6H 2 O 0.036g, measure 1.12mL of tetraethyl orthosilicate, add 30mL of anhydrous ethanol, and dissolve to obtain liquid A, wherein the mass ratio of tetraethyl orthosilicate to alcohol is 0.02:1;
[0094] (2) Weigh 3.15 g Ba(OH) in a beaker 2 8H 2 O, added to a mixed solution of 15 mL of water and 30 mL of anhydrous ethanol, heated in a water bath at 80 °C and stirred for 30 min to obtain solution B; wherein Ba(OH) 2 8H 2 The mass ratio of O to alcohol-water solvent is 0.05:1. In terms of mass fraction, the mass of water is 32% of that of alcohol;
[0095] (3) Add liquid A dropwise into the above liquid B, stir rapidly, and maintain the system temperature during the addition process. 3+ The percentage of the molar number of barium hydroxide in liquid B is 1%. After the titration of liquid A is completed, react for 2 hours, let it stand for 24 hours, centrifuge for 20 minutes and separate the solid and liquid to obtain a solid phase, put it in a drying oven for drying, and grind it in a mortar to obtain a powder after it is completely dried.
[0096] (4) The obtained powder was sintered in a muffle furnace at 600°C and kept at this temperature for 2 h, and then cooled to room temperature to obtain a nano-phosphor powder. The PL spectrum thereof was measured. Figure 8 As shown, the characteristic red color of trivalent europium ions is displayed.
[0097] Example 10
[0098] A BaO-SiO-based 2 The low-temperature synthesis method of nano-phosphor powder of the system specifically comprises the following steps:
[0099] (1) Weigh EuCl 3 6H 2 O 0.036g, measure 1.12mL of tetraethyl orthosilicate, add 30mL of anhydrous ethanol, and dissolve to obtain liquid A, wherein the mass ratio of tetraethyl orthosilicate to alcohol is 0.02:1;
[0100] (2) Weigh 3.15 g Ba(OH) in a beaker 2 8H 2O, added to a mixed solution of 15 mL of water and 30 mL of anhydrous ethanol, heated in a water bath at 80 °C and stirred for 30 min to obtain solution B; wherein Ba(OH) 2 8H 2 The mass ratio of O to alcohol-water solvent is 0.05:1. In terms of mass fraction, the mass of water is 32% of that of alcohol;
[0101] (3) Add liquid A dropwise into the above liquid B, stir rapidly, and maintain the system temperature during the addition process. 3+ The percentage of the molar number of barium hydroxide in liquid B is 1%. After the titration of liquid A is completed, react for 2 hours, let it stand for 24 hours, centrifuge for 20 minutes and separate the solid and liquid to obtain a solid phase, put it in a drying oven for drying, and grind it in a mortar to obtain a powder after it is completely dried.
[0102] (4) The obtained powder was sintered in a muffle furnace at 700°C and kept at this temperature for 2 h, and then cooled to room temperature to obtain a nano-phosphor powder. The XRD, SEM, and PL spectra thereof were measured. The XRD spectrum was as follows: Figure 6 As shown, the diffraction peaks all correspond well to the standard card, indicating that after sintering, the sample is transformed into a pure phase Ba 2 SiO 4 The higher the sintering temperature, the better the sample peak correspondence and the more main peak phases. Figure 7 Similarly, after sintering at 700℃, the powder particles are very fine, and the grain size is very small, only a dozen nanometers. Its PL spectrum is as follows Figure 8 As shown, the characteristic red color of trivalent europium ions is displayed.
[0103] Embodiment 11
[0104] A BaO-SiO-based 2 The low-temperature synthesis method of nano-phosphor powder of the system specifically comprises the following steps:
[0105] (1) Weigh EuCl 3 6H 2 O 0.036g, measure 1.12mL of tetraethyl orthosilicate, add 30mL of anhydrous ethanol, and dissolve to obtain liquid A, wherein the mass ratio of tetraethyl orthosilicate to alcohol is 0.02:1;
[0106] (2) Weigh 3.15 g Ba(OH) in a beaker 2 8H 2 O, added to a mixed solution of 15 mL of water and 30 mL of anhydrous ethanol, heated in a water bath at 80 °C and stirred for 30 min to obtain solution B; wherein Ba(OH) 2 8H 2The mass ratio of O to alcohol-water solvent is 0.05:1. In terms of mass fraction, the mass of water is 32% of that of alcohol;
[0107] (3) Add liquid A dropwise into the above liquid B, stir rapidly, and maintain the system temperature during the addition process. 3+ The percentage of the molar number of barium hydroxide in liquid B is 1%. After the titration of liquid A is completed, react for 2 hours, let it stand for 24 hours, centrifuge for 20 minutes and separate the solid and liquid to obtain a solid phase, put it in a drying oven for drying, and grind it in a mortar to obtain a powder after it is completely dried.
[0108] (4) The obtained powder was sintered in a muffle furnace at 800°C and kept at this temperature for 2 h, and then cooled to room temperature to obtain a nano-phosphor powder. The XRD, SEM, and PL spectra thereof were measured. The XRD spectrum was as follows: Figure 6 As shown, the diffraction peaks all correspond well to the standard card, indicating that after sintering, the sample is transformed into a pure phase Ba 2 SiO 4 The higher the sintering temperature, the better the sample peak correspondence and the more main peak phases. Figure 7 Similarly, after sintering at 800℃, the powder is very fine and the grain size is very small, only a dozen nanometers. Its PL spectrum is as follows Figure 8 As shown, the characteristic red color of trivalent europium ions is displayed.
[0109] Example 12
[0110] A BaO-SiO-based 2 The low-temperature synthesis method of nano-phosphor powder of the system specifically comprises the following steps:
[0111] (1) Weigh EuCl 3 6H 2 O 0.036g, measure 1.12mL of tetraethyl orthosilicate, add 30mL of anhydrous ethanol, and dissolve to obtain liquid A, wherein the mass ratio of tetraethyl orthosilicate to alcohol is 0.02:1;
[0112] (2) Weigh 3.15 g Ba(OH) in a beaker 2 8H 2 O, added to a mixed solution of 15 mL of water and 30 mL of anhydrous ethanol, heated in a water bath at 80 °C and stirred for 30 min to obtain solution B; wherein Ba(OH) 2 8H 2 The mass ratio of O to alcohol-water solvent is 0.05:1. In terms of mass fraction, the mass of water is 32% of that of alcohol;
[0113] (3) Add liquid A dropwise into the above liquid B, stir rapidly, and maintain the system temperature during the addition process. 3+The percentage of the molar number of barium hydroxide in liquid B is 1%. After the titration of liquid A is completed, react for 2 hours, let it stand for 24 hours, centrifuge for 20 minutes and separate the solid and liquid to obtain a solid phase, put it in a drying oven for drying, and grind it in a mortar to obtain a powder after it is completely dried.
[0114] (4) The obtained powder was sintered in a muffle furnace at 900°C and kept at this temperature for 2 h, and then cooled to room temperature to obtain a nano-phosphor powder. The PL spectrum thereof was measured. Figure 8 As shown, the characteristic red color of trivalent europium ions is displayed.
[0115] Example 13
[0116] A BaO-SiO-based 2 The low-temperature synthesis method of nano-phosphor powder of the system specifically comprises the following steps:
[0117] (1) Weigh EuCl 3 6H 2 O 0.036g, measure 1.12mL of tetraethyl orthosilicate, add 30mL of anhydrous ethanol, and dissolve to obtain liquid A, wherein the mass ratio of tetraethyl orthosilicate to alcohol is 0.02:1;
[0118] (2) Weigh 3.15 g Ba(OH) in a beaker 2 8H 2 O, added to a mixed solution of 15 mL of water and 30 mL of anhydrous ethanol, heated in a water bath at 80 °C and stirred for 30 min to obtain solution B; wherein Ba(OH) 2 8H 2 The mass ratio of O to alcohol-water solvent is 0.05:1. In terms of mass fraction, the mass of water is 32% of that of alcohol;
[0119] (3) Add liquid A dropwise into the above liquid B, stir rapidly, and maintain the system temperature during the addition process. 3+ The percentage of the molar number of barium hydroxide in liquid B is 1%. After the titration of liquid A is completed, react for 2 hours, let it stand for 24 hours, centrifuge for 20 minutes and separate the solid and liquid to obtain a solid phase, put it in a drying oven for drying, and grind it in a mortar after complete drying to obtain a powder with a mass of 2.2g;
[0120] (4) The obtained powder was mixed with 0.0015 g of graphite powder, and then placed in a muffle furnace and sintered at 900°C for 2 h. The powder was cooled to room temperature to obtain a nano-phosphor powder, and its SEM and PL spectra were measured. Fig. 9 As shown in the figure, after sintering at 900℃, the powder is very fine and the grain size is very small, only a dozen nanometers. Its PL spectrum is as follows Fig.10 As shown, the characteristic color of divalent europium ions is displayed.
[0121] Embodiment 14
[0122] A BaO-SiO-based 2 The low-temperature synthesis method of nano-phosphor powder of the system specifically comprises the following steps:
[0123] (1) Weigh EuCl 3 6H 2 O 0.072g, measure 1.12mL of tetraethyl orthosilicate, add 30mL of anhydrous ethanol, dissolve and prepare liquid A, wherein the mass ratio of tetraethyl orthosilicate to alcohol is 0.02:1;
[0124] (2) Weigh 3.15 g Ba(OH) in a beaker 2 8H 2 O, added to a mixed solution of 15 mL of water and 30 mL of anhydrous ethanol, heated in a water bath at 80 °C and stirred for 30 min to obtain solution B; wherein Ba(OH) 2 8H 2 The mass ratio of O to alcohol-water solvent is 0.05:1. In terms of mass fraction, the mass of water is 32% of that of alcohol;
[0125] (3) Add liquid A dropwise into the above liquid B, stir rapidly, and maintain the system temperature during the addition process. 3+ The percentage of the molar number of barium hydroxide in liquid B is 2%. After the titration of liquid A is completed, react for 2 hours, let it stand for 24 hours, centrifuge for 20 minutes and separate the solid and liquid to obtain a solid phase, put it in a drying oven for drying, and grind it in a mortar after complete drying to obtain a powder with a mass of 2.2g;
[0126] (4) The obtained powder was mixed with 0.003 g of graphite powder, and then placed in a muffle furnace and sintered at 900°C for 2 h. The powder was cooled to room temperature to obtain a nano-phosphor. The PL spectrum was measured. Fig.10 As shown, the characteristic color of divalent europium ions is displayed.
[0127] Embodiment 15
[0128] A BaO-SiO-based 2 The low-temperature synthesis method of nano-phosphor powder of the system specifically comprises the following steps:
[0129] (1) Weigh EuCl 3 6H 2 O 0.108g, measure 1.12mL of tetraethyl orthosilicate, add 30mL of anhydrous ethanol, dissolve and prepare liquid A, wherein the mass ratio of tetraethyl orthosilicate to alcohol is 0.02:1;
[0130] (2) Weigh 3.15 g Ba(OH) in a beaker 2 8H2 O, added to a mixed solution of 15 mL of water and 30 mL of anhydrous ethanol, heated in a water bath at 80 °C and stirred for 30 min to obtain solution B; wherein Ba(OH) 2 8H 2 The mass ratio of O to alcohol-water solvent is 0.05:1. In terms of mass fraction, the mass of water is 32% of that of alcohol;
[0131] (3) Add liquid A dropwise into the above liquid B, stir rapidly, and maintain the system temperature during the addition process. 3+ The percentage of the molar number of barium hydroxide in liquid B is 3%. After the titration of liquid A is completed, it is aged for 2 hours, then allowed to stand for 24 hours, centrifuged for 20 minutes and separated into solid and liquid to obtain a solid phase, which is placed in a drying oven for drying. After complete drying, it is ground in a mortar to obtain a powder with a mass of 2.2g.
[0132] (4) The obtained powder was mixed with 0.0045 g of graphite powder, placed in a muffle furnace and sintered at 800°C for 2 h, cooled to room temperature, and a nano-phosphor powder was obtained. The PL spectrum was measured. Fig.10 As shown, the characteristic color of divalent europium ions is displayed.
[0133] Example 16
[0134] A BaO-SiO-based 2 The low-temperature synthesis method of nano-phosphor powder of the system specifically comprises the following steps:
[0135] (1) Weigh EuCl 3 6H 2 O 0.018g, measure 1.12mL of tetraethyl orthosilicate, add 30mL of anhydrous ethanol, and dissolve to obtain liquid A, wherein the mass ratio of tetraethyl orthosilicate to alcohol is 0.02:1;
[0136] (2) Weigh 3.15 g Ba(OH) in a beaker 2 8H 2 O, added to a mixed solution of 15 mL of water and 30 mL of anhydrous ethanol, heated in a water bath at 80 °C and stirred for 30 min to obtain solution B; wherein Ba(OH) 2 8H 2 The mass ratio of O to alcohol-water solvent is 0.05:1. In terms of mass fraction, the mass of water is 32% of that of alcohol;
[0137] (3) Add liquid A dropwise into the above liquid B, stir rapidly, and maintain the system temperature during the addition process. 3+The percentage of the molar number of barium hydroxide in solution B is 0.5%. After the titration of solution A is completed, it is aged for 2 hours, then allowed to stand for 24 hours, centrifuged for 20 minutes and separated into solid and liquid to obtain a solid phase, which is placed in a drying oven for drying. After complete drying, it is ground in a mortar to obtain a powder with a mass of 2.2 g.
[0138] (4) The obtained powder was mixed with 0.0045 g of graphite powder, placed in a muffle furnace and sintered at 900° C. for 2 h, and then cooled to room temperature to obtain a nano-phosphor powder. The XRD and PL spectra were measured. The XRD spectra were as follows: Figure 6 As shown, the diffraction peaks all correspond well to the standard card, indicating that after sintering, the sample is transformed into a pure phase Ba 2 SiO 4 PL spectrum is as follows Fig.10 As shown, the characteristic color of divalent europium ions is displayed.
Claims
1. A low-temperature synthesis method of nano phosphor based on BaO-SiO2 system, characterized in that: The specific steps include: (1) dissolving tetraethyl orthosilicate and a salt of an activator element in alcohol to prepare liquid A; (2) grinding barium hydroxide, adding it to alcohol or a mixed solvent of alcohol and water to prepare liquid B, and heating it; (3) adding liquid A dropwise into the liquid B to react, maintaining the system temperature and stirring continuously during the addition process. After the titration of liquid A is completed, the reaction is continued for a period of time, and the system is allowed to stand, and then the solvent is removed from the system to obtain a solid phase, the components of which are BaH2SiO4 nanocrystals and residual barium hydroxide; (4) calcining the obtained solid phase, and then keeping the temperature to obtain nano phosphor powder; In the step (1), the activator elements are rare earth elements such as Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, and Yb, and transition elements such as V, Cr, and Mn; The salt of the activator element refers to an organic acid salt or an inorganic acid salt of the activator element, the organic acid is formic acid or acetic acid, and the inorganic acid is sulfuric acid, hydrochloric acid or nitric acid.
2. The method for low-temperature synthesis of nano phosphor based on BaO-SiO2 system according to claim 1, characterized in that: In the steps (1) and (2), the alcohol is a pure solution selected from one or more of ethanol, ethylene glycol, propanol, glycerol, and butanol. When multiple alcohols are selected, the multiple alcohols can be in any proportion.
3. The low-temperature synthesis method of nano phosphor based on BaO-SiO2 system according to claim 1, characterized in that: In the step (1), the mass ratio between tetraethyl orthosilicate and alcohol is (0.01-50):
1.
4. The method for low-temperature synthesis of nano phosphor based on BaO-SiO2 system according to claim 1, characterized in that: In the step (2), the ratio of the molar number of the added barium hydroxide to the molar number of the ethyl orthosilicate in the step (1) is set according to the Ba:Si ratio in the target silicate.
5. The method for low-temperature synthesis of nano phosphor based on BaO-SiO2 system according to claim 1, characterized in that: In the step (2), the mass ratio of barium hydroxide to alcohol or alcohol-water solvent is (0.01-10):1; in the alcohol or alcohol-water mixed solvent, the mass of water is 0-35% of the mass fraction of the alcohol.
6. The method for low-temperature synthesis of nano phosphor based on BaO-SiO2 system according to claim 1, characterized in that: In the step (2), the heating temperature is 40 to 90° C. and the heating time is 20 to 600 min.
7. The low-temperature synthesis method of nano phosphor based on BaO-SiO2 system according to claim 1, characterized in that: In the step (3), the ratio of the salt of the activator element in liquid A to the barium hydroxide in liquid B is: the percentage of the molar number of metal ions in the salt of the activator element to the molar number of barium hydroxide is 0.05-10%; The reaction time is 20 to 600 minutes, and the standing time is 1 to 48 hours; the method of removing the solvent is evaporation, vacuum drying, centrifugal separation or filter pressing.
8. The method for low-temperature synthesis of nano phosphor based on BaO-SiO2 system according to claim 1, characterized in that: In the step (4), the calcination temperature is 500 to 1200° C., and the insulation time is 60 to 600 minutes.
9. The method for low-temperature synthesis of nano phosphor based on BaO-SiO2 system according to claim 1, characterized in that: In the step (4), when the activator cations in the solid phase need to be reduced, calcination is performed under a protective atmosphere, or a reducing agent is mixed into or placed aside the solid phase.
10. The method for low-temperature synthesis of nano phosphor based on BaO-SiO2 system according to claim 9, characterized in that: The protective atmosphere is nitrogen, hydrogen or argon; the reducing agent is aluminum powder, iron powder or carbon powder. When carbon powder is used as the reducing agent, the carbon powder is mixed with the solid phase or used aside. When other reducing agents are used, they must be used aside. Calculated by mass fraction, the amount of reducing agent added shall not exceed 20% of the solid phase.